Healthcare Professionals’ Knowledge, Attitudes, and Practices Towards Stem Cell Therapy for Sarcopenia: A Cross-Sectional Study in Beijing - Wang Y; Wang Z; Gao Y; Zheng T; Liu T (Journal of Multidisciplinary Healthcare)
Yao Wang,1 Zhe Wang,2 Yanan Gao,3 Tianru Zheng,1 Tingting Liu1 1Geriatrics Department, Beijing Geriatric Hospital, Beijing, 100095, People’s Republic of China; 2Rehabilitation and Geriatric Department, Beijing Tongren Hospital Mentougou Campus, Capital Medical University, Beijing, 102300, People’s Republic of China; 3Rehabilitation Medicine Department, Beijing Geriatric Hospital, Beijing, 100095, People’s Republic of ChinaCorrespondence: Yao Wang, Geriatrics Department, Beijing Geriatric Hospital, Beijing, 100095, People’s Republic of China, Tel +86-18910691845, Email 1658421358@qq.comBackground: Sarcopenia significantly impacts the aging population, and this study investigates healthcare professionals’ knowledge, attitudes, and practices (KAP) towards stem cell therapy for sarcopenia.Methods: A cross-sectional study was conducted between January 1, 2024, and March 10, 2024, in medical institutions across Beijing. The study included healthcare professionals aged 18– 70 years who completed a self-designed KAP questionnaire (Cronbach’s α=0.917). Positive KAP was defined as scoring above 80% of the total score for each dimension.Results: A total of 451 healthcare professionals participated in the study, with 66.7% female and 41.0% aged 40– 49 years. The knowledge, attitude, and practice were 18.00 [10.00, 24.00] (possible range: 12– 24), 25.00 [23.00, 30.00] (possible range: 6– 30), and 21.00 [16.00, 30.00] (possible range: 7– 35), respectively. Of these respondents, 13.7% were healthcare workers in the geriatrics department, who had a positive knowledge score of 22.00 [14.00, 24.00] and a positive attitude score of 29.50 [24.00, 30.00], but their practice scores remain moderate at 27.00 [20.00, 35.00]. Additionally, 140 (31.0%) had treated sarcopenia patients within six months and 277 (61.4%) were employed at public tertiary hospitals with positive knowledge. Multivariate logistic regression indicated that not having treated patients with sarcopenia in the past six months was independently associated with poor knowledge (OR = 0.30, 95% CI: [0.15, 0.62], p = 0.001). Mediating effect analysis showed that knowledge directly affected both attitude (β = 0.475, p < 0.001) and practice (β = 0.127, p = 0.004), and indirectly influenced practice through attitude (β = 0.296, p < 0.001).Conclusion: Healthcare professionals exhibited inadequate knowledge, positive attitudes and inactive practices towards stem cell therapy for sarcopenia. Disease-related healthcare has positive knowledge, but moderate practice. Educational programs are essential to improve knowledge and foster proactive practices among healthcare professionals regarding stem cell therapy for sarcopenia.Keywords: knowledge, attitude, practice, healthcare professional, stem cell therapy, sarcopenia